2018
DOI: 10.1097/psy.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Brain Correlates of Mental Stress-Induced Myocardial Ischemia

Abstract: These findings suggest that mental stress-induced myocardial ischemia is associated with activation in brain areas involved in the stress response and autonomic regulation of the cardiovascular system. Altered brain reactivity to stress could possibly represent a mechanism through which stress leads to increased risk of CAD-related morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 119 publications
(96 reference statements)
3
50
0
1
Order By: Relevance
“…Evidence for the effects of psychological stress on neurohormonal systems following exposure to childhood trauma has been demonstrated previously, with increased hypothalamic-pituitary-adrenal axis response to both traumatic memory stressors in women with abuse-related posttraumatic stress disorder (Elzinga et al, 2003) and public speaking stressors in women with abuse and depression (Heim et al, 2000). Previously, in CAD patients, we have shown that mental stress activates areas within the inferior frontal gyrus and parietal cortex while deactivating areas within the pre-and postcentral gyrus, cerebellum, fusiform gyrus, and lingual gyrus (Bremner et al, 2018). Thus, mental stress appears to modulate brain activity in limbic, cognitive, and autonomic brain areas responding to the dual cognitive and emotional stress elicited by the tasks.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…Evidence for the effects of psychological stress on neurohormonal systems following exposure to childhood trauma has been demonstrated previously, with increased hypothalamic-pituitary-adrenal axis response to both traumatic memory stressors in women with abuse-related posttraumatic stress disorder (Elzinga et al, 2003) and public speaking stressors in women with abuse and depression (Heim et al, 2000). Previously, in CAD patients, we have shown that mental stress activates areas within the inferior frontal gyrus and parietal cortex while deactivating areas within the pre-and postcentral gyrus, cerebellum, fusiform gyrus, and lingual gyrus (Bremner et al, 2018). Thus, mental stress appears to modulate brain activity in limbic, cognitive, and autonomic brain areas responding to the dual cognitive and emotional stress elicited by the tasks.…”
Section: Introductionsupporting
confidence: 58%
“…The difficulty of mental math was increased until participants incorrectly answered three successive problems. The stressful public speaking task required participants to prepare (two minutes) and present (two minutes) a speech in response to two stressful interpersonal situations (Bremner et al, 2018). The speech was presented to a video camera and audience wearing white coats and participants were told the content and duration would be evaluated.…”
Section: Mental Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon implied that we should consider individual differences in the consequence caused by different types of mental stress task, which is consistent with Bremner et al's study. Bremner [41] conducted a study with the intent of revealing the association between brain and MSIMI. It was found that mental arithmetic was associated with left insula activation, while public speaking was associated with right pre/ post-central gyrus and middle temporal gyrus activation.…”
Section: Diagnostic Methods Of Msimimentioning
confidence: 99%